2014
DOI: 10.1007/978-3-662-43459-8_8
|View full text |Cite
|
Sign up to set email alerts
|

Designing Project Management for Global Software Development

Abstract: Abstract. Software development in distributed teams remains challenging despite rapid technical improvement in tools for communication and collaboration across distance. The challenges stem from geographical, temporal and sociocultural distance and manifest themselves in a variety of difficulties in the development projects. This study has identified a range of difficulties described in the literature of global software development, lacking sufficient solutions. In particular, advice for project managers is la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 44 publications
(63 reference statements)
0
1
0
Order By: Relevance
“…Tjørnehøj et al [38] tried to found well management and team members' related hurdles existed in GSD environment. Their contribution is concerned with providing formal and informal procedures for solving global barriers related to the managerial staff to ensure the project's success.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Tjørnehøj et al [38] tried to found well management and team members' related hurdles existed in GSD environment. Their contribution is concerned with providing formal and informal procedures for solving global barriers related to the managerial staff to ensure the project's success.…”
Section: Literature Reviewmentioning
confidence: 99%